Sustained Delivery of a Monoclonal Antibody against SARS-CoV-2 by Microencapsulated Cells: A Proof-of-Concept Study - Assem Ashimova; Askhat Myngbay; Sergey Yegorov; Baurzhan Negmetzhanov; Irina Kadyrova; Angelina Yershova; Ulpan Kart; Matthew S. Miller; Gonzalo Hortelano (MDPI AG, 2022)
Background: Monoclonal antibody (mAb) therapy is a promising antiviral intervention for Coronovirus disease (COVID-19) with a potential for both treatment and prophylaxis. However, a major barrier to implementing mAb therapies in clinical practice is the intricate nature of mAb preparation and delivery. Therefore, here, in a pre-clinical model, we explored the possibility of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mAb delivery using a mAb-expressing encapsulated cell system. Methods: Murine G-8 myoblasts were transfected with plasmids coding for the heavy and light chains of CR3022, a well-characterized SARS-CoV-2 mAb that targets the Spike receptor binding domain (RBD), and then encapsulated into alginate microcapsules. The microcapsules were then intraperitoneally implanted into immunocompetent (C57/BL6J) mice and changes in circulating CR3022 titres were assessed. The in vitro and ex vivo characterization of the mAb was performed using western blotting, RBD ELISA, and microscopy. Results: Transfected G-8 myoblasts expressed intact CR3022 IgG at levels comparable to transfected HEK-293 cells. Cell encapsulation yielded microcapsules harbouring approximately 1000 cells/capsule and sustainably secreting CR3022 mAb. Subsequent peritoneal G-8 microcapsule implantation into mice resulted in a gradual increase of CR3022 concentration in blood, which by day 7 peaked at 1923 [1656-2190] ng/mL and then gradually decreased ~4-fold by day 40 post-implantation. Concurrently, we detected an increase in mouse anti-CR3022 IgG titers, while microcapsules recovered by day 40 post-implantation showed a reduced per-microcapsule mAb production. Summary: We demonstrate here that cell microencapsulation is a viable approach to systemic delivery of intact SARS-CoV-2 mAb, with potential therapeutic applications that warrant further exploration.